Diplodia populicola sp. nov. causing branch canker of poplar in Beijing, China - Zhang, Zhe; Jiao, Ning; Guo, Lin-Na; Wang, Jia-Wen; Zhang, Ying (Phytotaxa, 2025)
Poplar is a vital timber species, but branch canker caused by Botryosphaeriaceae species are widespread and severe in China, leading to substantial economic losses. In this study, two fungal isolates morphologically classified under Botryosphaeriaceae were obtained from cankered poplar branches collected in the Wenyu River region of Beijing. Morphological characteristics and phylogenetic analyses based on ITS, tef1-α, and tub2 identified these strains as a novel species, named Diplodia populicola. Diplodia populicola differs from its sister species, D. seriata, in having smaller conidia. Koch’s postulates confirmed that this species can induce canker on poplar branches.